Research and manufacture of the mini gamma camera using multi-anode photo multiplier tube (Ma-PMT) - Ha, Bui; Dang Nguyen The, Duy; Nguyen Tuan, Hoang; Vu Thu, Trang; Lai Viet, Hai (Nuclear Science and Technology, 2026)
A Gamma camera is an imaging technique that captures gamma radiation emitting from the radiation sources. In this paper, the authors built a Mini-Gamma camera system using a micro photomultiplier tube (µPMT) H12700, signal processing circuit, and control software as self-designed products. The Gamma camera system includes four parts: collimator, scintillator NaI(Tl), µPMT, processing, and controller boards. The electronic system had preamplifiers used to convert negative signals from the µPMT to positive signals, integrators used to sharpen the signal from the preamplifier, and an amplifier circuit to amplify the signal from the preamplifier, a position detection circuit to detect the location of radiation interaction in the crystal. All circuits in the Mini-Gamma camera system are optimized to achieve the best projection image quality. In this paper, the lab-built Mini-Gamma Camera has an energy resolution of 45% at 60 keV gamma rays, the affected field of the camera is 42×48.5 mm2, and the spatial resolution of the image is around 1 mm.